Analysis of Advective–Diffusive Transport in Complex Mixing Devices by the Diffusive Mapping Method. Issue 4 (1st April 2015) - Gorodetskyi, Oleksandr; Vivat, Iaroslav; Speetjens, Michel F. M.; Anderson, Patrick D.
<x xml:space="preserve">Abstract</x> The present study concerns analysis of advective–diffusive transport in prototypical industrial mixing devices by the diffusive mapping method. The latter is a recent extension of the conventional mapping method for distributive mixing and enables application of this efficient technique to mixing flows, including molecular diffusion. Primary challenge is detailed numerical analysis of flow and mixing properties inside realistic systems with complex geometries. This is performed by combining the diffusive mapping method with a sophisticated computational scheme for flow simulations in domains with complex (moving) boundaries: the eXtended Finite Element Method (XFEM). The mixing properties are investigated through spectral analysis of the advective–diffusive transport by way of eigenmode decomposition of the mapping matrix. Key topic is the correlation between the evolution of concentration fields and invariant Lagrangian structures in the flow field.<inline-graphic xlink:href="ark:/27927/pgj2fnfw5r6" content-type="mats201400083-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />